Putting Buddhism to work : - Inoue, Shin'ichi (Kodansha International, 1997)
The challenge of the twenty-first century lies in developing a new type of economics that will save the earth rather than destroy it. Shinichi Inoue argues that while economics will continue to be based on the "free market, " the interpretation of the word "free" can be different from that normally accepted in the West, where freedom centers around the rights of the individual. In contrast, in the Buddhist view freedom ensues when all personal desires are mastered or superseded. In this way, a Buddhist approach involves understanding that economics and a moral and spiritual life are neither separate nor mutually exclusive. Buddhist economics avoids conflict with nature and operates in a way that is spiritually rich, socially beneficial, as well as environmentally friendly. In effect, it is an economics that shows us how to move beyond the unfortunate compartmentalization of our lives symptomatic of the present age to a more holistic vision of life. Drawing on his experience as the head of a major Japanese bank, Shinichi Inoue shows how the management of large enterprises can be reconciled with the compassionate teachings of Buddhism. Throughout this book, he also examines successful companies where innovative management outlooks have been adopted, and he illustrates his stimulating approach to business with abundant anecdotes.